FSQCN: Fast and Simple Quantized Congestion Notification in Data Center Ethernet - Ruan, Chang; Wang, Jianxin; Jiang, Wanchun (Proceedings of the International Conference on Distributed Computing Systems, 2016)
Currently, Quantized Congestion Notification (QCN) has been accepted as the standard layer 2 congestion control protocol in Data Center Ethernet. Although the good performance of QCN has been validated in many experiments, we find that QCN has two drawbacks. First, the incomplete binary search in QCN fails to find the proper sending rate, leading to complicate supplement mechanisms. Second, in face of unknown network environment, the rate setting of QCN is inconsistent. Consequently, QCN spends much time on acquiring the spare bandwidth. To address theses problems, we propose the Fast and Simple QCN (FSQCN), following the same framework as QCN. FSQCN complements the binary search and removes other complicate supplement mechanisms in QCN. Thus, FSQCN is much simpler than QCN. Moreover, FSQCN resets the sending rate to the link rate explicitly when the switch detects spare bandwidth. Extensive simulations validate that FSQCN controls the queue length well like QCN and responds faster than QCN.